Optimizing the Management of Educational Facilities and Infrastructure in Vocational High Schools - Garatta, Mega Rani Jaya; Akib, Haedar; Salam, Rudi (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
The management of educational facilities plays a crucial role in supporting effective teaching and learning processes in schools. It is essential for optimizing available resources to ensure that these facilities are fully utilized, even with existing limitations. This study aims to investigate the optimization of educational facility management at SMK YPLP PGRI 1 Makassar, with a focus on the library, the computer lab for the MPLB program, and classroom XII MPLB 1, as well as to identify the supporting and inhibiting factors in the management of these educational facilities. This research employs a descriptive qualitative approach, with data collected through observations, interviews, and documentation, and analyzed using data collection, data condensation, data presentation, and conclusion drawing. The findings show that the optimization of facility management at SMK YPLP PGRI 1 Makassar has been effectively implemented, as it is carried out systematically with clear optimization efforts. Planning is conducted annually in a participatory manner by various school stakeholders and is based on needs and priority scales. Procurement is carried out according to plan and in stages based on urgent needs. Organization is managed through inventory, storage, and maintenance with active involvement from all parties. The use of facilities is effective and in accordance with their functions, with a scheduled and orderly system, while disposal is carried out functionally by removing damaged items from the inventory list, although it lacks oficial administrative documentation. Key supporting factors include cooperation among stakeholders, student participation, and budget support. Challenges include space limitations and security issues. Therefore, the optimization of facility management is not solely determined by the availability of resources but also by the school’s ability to maximize the utilization, organization, and maintenance of these resources despite limitations.